2022
DOI: 10.3390/ijms23084172
|View full text |Cite
|
Sign up to set email alerts
|

Squalene through Its Post-Squalene Metabolites Is a Modulator of Hepatic Transcriptome in Rabbits

Abstract: Squalene is a natural bioactive triterpene and an important intermediate in the biosynthesis of sterols. To assess the effect of this compound on the hepatic transcriptome, RNA-sequencing was carried out in two groups of male New Zealand rabbits fed either a diet enriched with 1% sunflower oil or the same diet with 0.5% squalene for 4 weeks. Hepatic lipids, lipid droplet area, squalene, and sterols were also monitored. The Squalene administration downregulated 9 transcripts and upregulated 13 transcripts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In the porcine model used in this study, the administration of the diet over a short period promoted NASH with an identical distribution of cellular ballooning grades 1 and 2, as determined by the steatosis activity fibrosis (SAF) score and FLIP algorithm [ 32 ]. The amount of squalene chosen was similar to that administered to rabbits, which induced changes in the hepatic transcriptome [ 30 ]. This amount would also represent an adapted metabolic rate of the 1% squalene-containing diets used in mice [ 29 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the porcine model used in this study, the administration of the diet over a short period promoted NASH with an identical distribution of cellular ballooning grades 1 and 2, as determined by the steatosis activity fibrosis (SAF) score and FLIP algorithm [ 32 ]. The amount of squalene chosen was similar to that administered to rabbits, which induced changes in the hepatic transcriptome [ 30 ]. This amount would also represent an adapted metabolic rate of the 1% squalene-containing diets used in mice [ 29 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human hepatocytes, squalene modified the expression of lipid metabolism genes, leading to crucially lower triacylglycerols and cholesterol content, when cellular uptake of fatty acids was increased [ 43 ]. In other models, squalene has been found to influence a cluster of genes related to lipid content [ 29 , 30 ]. The difference in responses could be related to species-specific expression patterns or to experimental settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Squalene, a biofunctional lipid compound, is reported to have diverse bioactivities ranging from cardioprotective, antioxidant, chemopreventive, anti-cancerous, anti-lipidemic, and membrane-stabilizing properties, among others [ 68 ]. A previous study showed that squalene could enhance serum high-density lipoprotein cholesterol levels and reduce oxidative stress [ 69 ]. It has been revealed that squalene and post-squalene metabolites are modulators of hepatic transcriptional changes in rabbits, thus protecting the liver against dysfunction [ 70 ].…”
Section: Bioactive Compoundsmentioning
confidence: 99%